Analysis of CLCNKB mutations at dimer‐interface, calcium‐binding site, and pore reveals a variety of functional alterations in ClC‐Kb channel leading to Bartter syndrome. Issue 4 (24th December 2019) - Bignon, Yohan; Sakhi, Imene; Bitam, Sara; Bakouh, Naziha; Keck, Mathilde; Frachon, Nadia; Paulais, Marc; Planelles, Gabrielle; Teulon, Jacques; Andrini, Olga
Abstract: Pathological missense mutations in CLCNKB gene give a wide spectrum of clinical phenotypes in Bartter syndrome type III patients. Molecular analysis of the mutated ClC‐Kb channels can be helpful to classify the mutations according to their functional alteration. We investigated the functional consequences of nine mutations in the CLCNKB gene causing Bartter syndrome. We first established that all tested mutations lead to decreased ClC‐Kb currents. Combining electrophysiological and biochemical methods in Xenopus laevis oocytes and in MDCKII cells, we identified three classes of mutations. One class is characterized by altered channel trafficking. p.A210V, p.P216L, p.G424R, and p.G437R are totally or partially retained in the endoplasmic reticulum. p.S218N is characterized by reduced channel insertion at the plasma membrane and altered pH‐sensitivity; thus, it falls in the second class of mutations. Finally, we found a novel class of functionally inactivated mutants normally present at the plasma membrane. Indeed, we found that p.A204T alters the pH‐sensitivity, p.A254V abolishes the calcium‐sensitivity. p.G219C and p.G465R are probably partially inactive at the plasma membrane. In conclusion, most pathogenic mutants accumulate partly or totally in intracellular compartments, but some mutants are normally present at the membrane surface and simultaneously show a large range of altered channel gating properties. Abstract : Molecular analysis of the mutated ClC‐Kb channels can be helpful to classify the mutations according to their functional alteration. We investigated the functional consequences of nine mutations in the CLCNKB gene causing Bartter syndrome. Most pathogenic mutants accumulate partly or totally in intracellular compartments, but some mutants are normally present at the membrane surface and simultaneously show a large range of altered channel gating properties.